Vision 2030 and prospects for network airlines in Saudi Arabia - Jimenez, Edgar; Ellis, Darren; Uyan, Berkcan (Elsevier, 2023)
The air transport industry in Saudi Arabia is experiencing rapid growth of late, fuelled in large part by the Kingdom's Vision 2030 aspirations and national development plan. This ambitious national vision seeks to diversify the Kingdom's economy, and in the process, develop and expand a wide range of industry and public sectors. Central to these plans is air transport, including not only the building of new airports and related transport infrastructure, along with expanding the wider travel and hospitality sectors, but also the launch of a new network airline in 2025 – Riyadh Air. This new airline will join current national flag carrier Saudia, and together they will play central roles in growing both the domestic and international air markets in the Kingdom, mainly out of the two main hubs Riyadh Airport (RUH) and Jeddah Airport (JED). The paper here aims to assess this coming network carrier duopoly, including the future prospects for both airlines as they seek to compete in a region, and indeed globally, against well-established legacy and flag carriers. Evidently, the future of network airlines in KSA could very well shape and determine prospects for the industry more generally for decades to come.
In: 12th International Conference on Air Transport – INAIR 2023, The Future of Aviation – is the Sky the Limit? Held: 15-17 November 2023, Tartu, Estonia
Keywords: Saudi Arabian air transport; Vision 2030; Middle East aviation; network airlines/carriers; duopoly